PENGARUH PENGETAHUAN TENTANG QRIS, KEMUDAHAN AKSES DAN KEMANFAATAN TERHADAP MINAT PENGGUNAAN QRIS SEBAGAI ALAT TRANSAKSI KEUANGAN PADA MAHASISWA GENERASI Z PERGURUAN TINGGI DI YOGYAKARTA - Cahyaningrum, Anissa; Martinus Budiantara (ITB AAS Indonesia Surakarta, 2025)
The objective of this research is to explore how knowledge regarding QRIS, the ease with which it can be accessed, and users’ perceptions of its usefulness shape the interest of Generation Z university students in Yogyakarta to use QRIS for financial transactions. This investigation uses a quantitative method, gathering first-hand data through a questionnaire distributed to 100 university students belonging to Gen Z in Yogyakarta. The data were then processed using multiple linear regression techniques. The analysis indicates that familiarity with QRIS significantly boosts students' willingness to use it. Likewise, both the simplicity of access and perceived utility play crucial roles in increasing their interest. These findings underline the need to raise awareness, improve accessibility, and amplify the perceived advantages of QRIS in order to promote its broader use among today’s digital-native youth. Keywords: Knowledge, Ease of Access, Perceived Usefulness, Interest, QRIS